Determination of Rilpivirine through LCMS/MS Method: A Novel Approach - Kumar, B. Raj; Subrahmanyam , K. V. (Novel Aspects on Pharmaceutical Research Vol. 5, 2023)
This chapter highlights a novel approach for Determination of Rilpivirine through LCMS/MS Method. Rilpivirine is a new non-nucleoside reverse transcriptase inhibitor (NNRTI) that is approved for HIV-1 treatment-naive adult patients in combination with other antiretroviral agents. Over a wide pH range, rilpivirine hydrochloride is essentially insoluble in water. The inactive components croscarmellose sodium, lactose monohydrate, magnesium stearate, polysorbate 20, povidone K30, and silicified microcrystalline cellulose are also found in each EDURANT tablet. Using a column Kinetex C18, 100x4.6mm, 2.6µ with a mobile phase containing a mixture of 0.1% Formic acid and Acetonitrile: Methanol: Isopropanol 65:15:25% v/v in ratio of (5:95) %v/v. The flow rate was 0.6 ml/min and effluent were monitored at 282 nm and a peak eluted at 2.06 min and column oven temperature was maintained ambient. Forced degradation was used to validate the optimised method for specificity, and it was discovered that the primary peak remained pure under all degradation circumstances, demonstrating that the approach was a stability indicating one. The method was linear in the range of 0.03 µg/ml to 0.14µg/ml and the correlation coefficient was found to be 0.9997. The method was also found to be accurate in 50 to 150% of test concentration. The Limit of Quantification of the method was found to be 10.7836 pg/ml. As the main intention of development of LCMS method is to detect and quantify Rilpivirine at lower concentration, Rilpivirine standard of 0.1PPM were prepared from standard stock solution. According to the most recent International Conference on Harmonisation (ICH) guidelines, a mass compatible liquid chromatographic technique was refined and validated for specificity, LOD, LOQ, linearity, accuracy, precision, intermediate precision, and robustness. The results of the study showed that the proposed method was found to be repeatable, precise, linear and accurate.